3D microstructural architecture of deformed glacigenic sediments associated with large‐scale glacitectonism, Jasmund Peninsula (NE Rügen), Germany. (16th March 2016) - Gehrmann, Anna; Hüneke, Heiko; Meschede, Martin; Phillips, Emrys
ABSTRACT: The Wissower Bach Syncline on the Jasmund Peninsula (NE Germany) has been examined to understand the complicated glacitectonic environment in the southern Baltic Sea region, comprising folds and thrust faults from the Weichselian–Pleniglacial. Soft‐sediment thin sections from a SW‐dipping thrust fault at the south‐western limb of the syncline between Cretaceous chalk (hangingwall) and Pleistocene deposits (footwall) were analysed using micromorphology and microstructural mapping. Within the diamicton bounding the fault, three different clast microfabrics were distinguished: an older, but dominant S1 fabric; a second S2 foliation orientated perpendicular to S1; and a younger subvertical S3 fabric. These fabrics developed during large‐scale folding and thrusting, subsequent fabric rotation adjacent to the thrust fault accompanied by dewatering of the diamicton and extension; the extension implies late‐stage reactivation and gravitational relaxation at the south‐western limb of the syncline as the ice retreated. The combination of a 3D microstructural model and the macroscale information has led to the development of a detailed model for the evolution of the Wissower Bach Syncline during glacitectonism and the localized reactivation of the associated thrusts in response to ice retreat. Moreover, this methodology provides a robust dataset on which to interpret the structural evolution of glacitectonic complexes.